An Effect of Coping Skill Training Program on Depression in Early Adolescents - Wattanapailin, Atirat; Pratum, Lalana; Sitthimongkol, Yajai (Nursing Science Journal of Thailand, 2011)
Purpose: To examine an effect of a coping skill training programon depression in early adolescents. Design: Experimental research. Methods: The study group consisted of 30 Mathayomsuksa 2 (8thgrade) students from a school in Chantaburi Province. They wererandomly assigned into an experimental group and a controlgroup, with 15 students each. Before the experiment, all 30subjects were assessed to complete the Children’s DepressionInventory. The experimental group then received the coping skilltraining program twice a week for 11 sessions. Each session lasted60-90 minutes. On the other hand, the control group received theusual care provided by the school. Both groups of subjects wereassessed to determine their depression again at post-interventionimmediately, one-month, and three-month follow-ups. Thedepression scores elicited from the subjects in the experimentalgroup were analyzed to compare the differences of mean scoresbetween pre and post – intervention and to compare thedifference of mean scores of depression between the experimentaland the control groups using a repeated-measures ANOVA. Main findings: The findings revealed that the mean score ofdepression of the subjects in the experimental group at postinterventionimmediately, one-month follow- up and threemonthfollow- up was lower than that at pre-intervention with astatistical significance (p < .001). Moreover, the mean score ofdepression of the subjects in the experimental group was lowerthan in the control group at three points of time: postintervention,one-month follow-up and three-month follow- upwith a statistical significance (p < .01, p < .01, and p < .05,respectively). Conclusion and recommendations: Based on the study findings,it is recommended that healthcare personnel who are involvedwith mental health care of adolescents should use the coping skilltraining program to prevent or reduce depression amongadolescents. Training should also be provided to equip theadolescents with skills to deal with negative thought as well asvarious stress management skills to enable them to effectivelycope with stress and prevent them from depression.